Tectonic Deformation of the Western Qilian Shan in Response to the North–South Crustal Shortening and Sinistral Strike-Slip of the Altyn Tagh Fault Inferred From Geomorphologic Data - Chen, Zhidan; Xu, Wenbin; Liu, Rui; Li, An; Koronovsky, N. V. (Frontiers in Earth Science, 2022)
The tectonic deformation of a series of NWW-trending compressional band-shaped mountains and fault zones in the Qilian Shan, northeastern Tibet, plays an important role in absorbing the north–south crustal shortening of the Tibetan Plateau and accommodating the sinistral strike-slip of the Altyn Tagh fault. However, the deformation pattern of these mountains and fault zones in response to crustal shortening and sinistral strike-slip remains to be investigated. In this study, we present the slope map and swath profiles of the western Qilian Shan extracted from high-resolution digital elevation model (DEM) data and the fluvial geomorphologic characteristics of the Baiyang river in the northwestern Qilian Shan. Our data indicate that the crustal uplift of the northern Qilian Shan is stronger than that of the central and southern ranges of the Qilian Shan because of the high-terrain relief and stronger erosion. In addition, the deformed terraces of the Baiyang river documented the activity of NWW-trending faults in the western Qilian Shan. Based on the longitudinal profiles and ages of the deformed river terraces, the vertical slip rates of the Changma, Yumen, and Bainan faults in the western Qilian Shan since ~60 ka were constrained to be 0.31 ± 0.06, 0.33 ± 0.02, and 0.24 ± 0.02 mm/a, respectively. Based on the comparison with previous studies, we noticed that the rate of the vertical slip since the Late Quaternary of the northern Qilian fault of 1.5–2 mm/a is significantly higher than that of the Changma fault of 0.3–0.6 mm/a, which matches the terrain relief in the Qilian Shan and demonstrates that the northern Qilian Shan has been rising faster than its southern ranges. From the slip rates of the NWW-trending faults in the western Qilian Shan, we suggest that the crustal shortening is widely distributed in the NWW-trending compressional orogenic belts and fault zones across the Qilian Shan, among which the northern Qilian Shan and its frontal thrust system absorb the greatest shortening amount, whereas strike-slip faults within the Qilian Shan accommodate most of the sinistral strike-slip of the Altyn Tagh fault.